2022
DOI: 10.3390/agronomy12102266
|View full text |Cite
|
Sign up to set email alerts
|

The PGPR Mechanisms of Salt Stress Adaptation and Plant Growth Promotion

Abstract: Worldwide crop productivity hampers severely due to the adverse effects of salinity. Global warming causes a rapid escalation of the salt-affected area, and new agricultural land is affected through saltwater intrusion. The ever-growing human population impulses to utilize the saline area for crop cultivation to ensure food security. Salinity resistance crops could be a promising substitute but with minor success because inappropriate tactics on saline soil management resulted in unsatisfactory yield. Salt-tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 141 publications
1
19
0
Order By: Relevance
“…This indicates that rhizobacteria from saline soil have a better ability to promote plant growth. The results of previous studies also showed that rhizobacteria from saline soils were better able to increase plant growth [11].…”
Section: Discussionmentioning
confidence: 82%
“…This indicates that rhizobacteria from saline soil have a better ability to promote plant growth. The results of previous studies also showed that rhizobacteria from saline soils were better able to increase plant growth [11].…”
Section: Discussionmentioning
confidence: 82%
“…The highest number of nodules plant 1 was observed in S. rostrata followed by S. aculeate (Irin and Biswas, 2021a) and plant growth promoting rhizobacteria (PGPR) are potential bioinoculants to enhance crop productivity in saline agriculture (Shultana et al, 2022). The free-living and symbiotic bacteria in nature can fix atmospheric N2 in salt stress conditions and contribute to plant growth (Sultana et al, 2022).…”
Section: Green Manure For Reclamation Of Salinitymentioning
confidence: 99%
“…In recent years, there has been increased interest in studying VOCs released by PGPR [ 19 , 20 , 21 , 22 , 23 , 24 ]. Many types of soil bacteria can emit mVOCs, although the type and quantity of the compounds released may differ between species and culture conditions [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%